PENERAPAN BUDAYA KERJA KAIZEN DI PT X KABUPATEN BANDUNG BARAT - Budi Prasetiyo; Ryan Supu Tauhid (Islamic University of Kalimantan MAB Banjarmasin, 2019)
Kaizen is a Japanese culture that means continuing to improve and improve quality in the workplace. This culture is applied by many Japanese companies in the world, especially manufacturing companies. ISO 9001 is a quality management control system (Total Quality Management / TQM) issued by the Internatinal Organization for Standardization. ISO 9001 emphasizes for organizations starting from top management to lower level in carrying out continuous improvement and improvement of work quality. The auxiliary tool used in this research is Quality Control Circle (QCC) which uses the PDCA concept and 7 tools. The QCC method is a method that can be used to control product quality and reduce the number of defective products. The results of this study are that the Kaizen work culture has not run effectively even though the impact on productivity and employee performance is very influential and from the results of this QCC it is evident that with the change in the new Operational Procedure Standards it can reduce the total percentage of defective goods compared to the previous periodKeywords: Kaizen, ISO 9001, Total Quality Management, PDCA, 7 Tools, Quality Control Circle